Correction of pancreatic insufficiency in young children with atopic dermatitis - I.G. Solodovnichenko; L.G. Voloshina; E.N. Babadzhanyan; E.V. Savitskaya (Zaslavsky O.Yu., 2016)
Introduction. Atopic dermatitis has a dominant place in the structure of the skin diseases of childhood (from 20 to 50% of patients with dermatosis children) that determines the interest of pediatricians and family doctors to improve the efficiency of treatment of this disease. Often, skin manifestations and severity are closely related to the gastrointestinal pathology, that occurs in 52% of patients with atopic dermatitis. Objective: evaluation of the effectiveness of the enzyme mini-tableted Ermital 10,000 for the compensation of pancreatic insufficiency in children with atopic dermatitis. Materials and methods. The study involved 36 children aged 3 to 6 years old with pancreatic insufficiency, against which the skin syndromes were observed in the form of atopic dermatitis. Clinical and paraclinical examination (clinical observations, scatology, the definition of IgE, amylase in serum and urine, ultrasound examination by S.I. Polyakova's method) was performed. Results. The inclusion of pancreatin enzyme medication of Ermital 10,000 into the complex treatment of children with atopic dermatitis had a good clinical effect observed in almost 90 % of patients. In 88.8 % of children coprogram performance on the 14th day of treatment was completely normal. Conclusions. The use of the enzyme medication of Ermital 10,000 in patients with atopic dermatitis contributed to the elimination of pain and dyspeptic syndromes, improvement of laboratory parameters of the pancreas functioning, a decrease of skin manifestations. The drug is well tolerated, does not cause side effects, consequently, it can be recommended for the correction of pancreatic insufficiency in children with atopic dermatitis.